USING DISCOVERY LEARNING MODEL TO IMPROVE WRITING SKILL ON EXPLANATION TEXT TO THE THIRD SEMESTER OF STUDENTS’ ECONOMY FACULTY OF TRIDINANTI UNIVERSITY PALEMBANG - Ria, Nita; Setiawan, Heru (English Community Journal, 2021)
The objective of the study was to find out whether or not there was a significant diffrence of writing skill on explanation text through schoology application between students’ economy faculty of tridinanti University Palembang who were taught by using discovery learning model and those who were not. The data were colleted through written test about expalanation text in pretest and posttest. The population of this study was the third semester students’ economy faculty of Tridinanti university Palembang, Experimental group consisted of 28 students and control group consisted of 28 students. This study used quasi experimental method. In this study the writers chose two classes as the experimental group and control group. The data were analyzed by using paired sample t-test and independent sample t-test. The result of the data analysis showed that the mean score post-test of experimental group was 67.10 and the mean score post-test of control group was 50.41. The result of paired sample t-test showed that the mean score of experimental group was 29.434 and 17.657 in control group. since the value of t-obtained was higher than the critical value of t-table. It showed that the null hypothesis was rejected and the alternative hypothesis was accpeted. It means that there was was significant different of writing skill students’ economy faculty of Tridinanti University Palembang who are taugh by using discovery learning model and those who were not.